Role of Fasting Mimicking Diet in Farnesoid x Receptor for Suppressing Epithelial-to-Mesenchymal Transition, Cell Cycle Progression, and Viability of Prostate Cancer Cells - Wrood Salim; sameh Arif, Inam; Talib Al-sudani, Basma (Iraqi Journal of Pharmaceutical Sciences, 2023)
The systemic and resistant nature of metastatic castration-resistant prostate cancers (mCRPC) renders it largely incurable even after intensive multimodal therapy. Proliferation, survival, and epithelial-mesenchymal transition (EMT) are three fundamental events that are deeply linked to carcinogenesis. Hence, it is necessary to find a new combination of several therapies, targeting those vital mechanisms without causing side effects. Significant research works have shown differential low expression of the metabolic Farnesoid X receptor (FXR) in primary and metastatic prostate cancer suggesting their importance in prostate pathogenesis. Obticholic acid (INT 747), a potent FXR agonist is widely used in primary biliary cholangitis, and Fasting mimicking Diet (FMD) both were drastically showed effects on different cancer progression. We hypothesized that FXR and FMD may inhibit proliferation and the metastatic phenotype in PC-3 prostate cancer cells. Analyses of the cell viability, cell cycle, migration, and matrigel invasion assays were performed to elucidate how INT 747 and /or FMD functions in prostate cancer. In this study, INT 747 treatment caused apoptotic morphological changes and significantly reduced the survival of PC-3 cells incubated in normal mediums. Furthermore, we showed that the combination of the INT 747 and FMD was much more harmful to cancer cells than the treatment with INT 747 or FMD alone. Moreover, our study showed that INT 747 either alone or combined with FMD robustly induced cell cycle arrest at the S phase. Interestingly, the combination treatment on PC-3 cells not only showed several lines of evidence of apoptotic cells death but also inhibited carcinogenic potential as evaluated by impairment of spheroid formation capacity and delayed wound healing and matrigel invasion. At the cellular level, FXR activation resulted in down-regulation of procaspase -3, vimentin, and MMP9, which triggers apoptotic cell death, cell cycle arrest, and switch from mesenchymal to an epithelial phenotype. Collectively, FXR activation alone markedly decreases, and when combined with FMD abrogates the survival and carcinogenic potential of metastatic prostate cancer cells.